DEVELOPING COUNTRIES AND PUBLIC TRANSPORT: ISSUES AND CHALLENGES - Suyono, Rudi Sugiono; Tamin, Ofyar Z.; Wibowo, Sony Sulaksono; Purboyo, Heru (FSTPT Indonesia, 2015)
Today motorization happens quite fast even faster in many cities in the world. The number of motor vehicles in the world is expected to reach about 1.3 billion by 2020, more than double the current number. In the case of Indonesia, in the past three decades, motorization and urbanization has become a trend in many cities - metropolitan city. Unlike developed countries, most developing countries do not have a mass transit system that adequate to suppress the increase in motorization in urban areas. This research try mapping issues and challenges of public transport plan, implementation and operation in developing countries by literature study’s methodology. Finding of this study, at least, there are 5 (five) issues in the relation with public transport in developing countries i.e. sustainability impact issues, multi-faceted actor in the public transport implementation (organization and institutional issues), need of public transport appraisal in strategic level issues, funding (budget constraint) issues, and competition and regulation issues. Then, there are some challenges of public transport implementation such as problem of political organization, problem of integrated transport planning, continuing need to develop appropriate pricing and charging devices and financing instruments, the matter of industrial structure, the issue of competitive system design, the perceived problem of affordability and problem of strategic choice, particularly in urban areas.